National culture and groups - Chen, Ya-Ru.; Mannix, Elizabeth A., 1960-; Neale, Margaret Ann.; Wageman, Ruth. (Bingley, U.K. : Emerald, 2006)
This volume is based on the premise that in an era of rapid globalization, while there is a great deal of convergence on many aspects of group processes and interactions across national cultures, it is the understanding and appreciation of the divergence among people of different national cultural backgrounds that make all the difference. Contributors to this volume address two broad important questions: Do our theories of groups and teams functioning apply universally? And how do our theories apply, if at all, in multicultural settings? In addition, this volume highlights new exciting topics in the cross-cultural area: power, time, creativity, emotions, networks, and multi-cultural diversity. Together, the chapters attest to the fact that study of national culture is flourishing and important. It not only informs but also modifies and enriches theories and research of group processes and social behavior. The collective effort in this book should stimulate further inquiry regarding the role of national culture in the increasingly globalized human experience. This book features an international representation. It addresses a variety of group processes. It investigates group processes in a multi-cultural environment (i.e., a global company).
Temporality in negotiations : a cultural perspective / Sungu Armagan, Manuel Portugal Ferreira, Bryan L. Bonner, Gerardo A. Okhuysen -- Culture, affect, and social influence in decision-making groups / Lu Wang, Lorna Doucet, Gregory Northcraft -- Question comprehension and response : implications of individualism and collectivism / Ayse K. Uskul, Daphna Oyserman -- Managing the intercultural interface : third cultures, antecedents, and consequences / Wendi L. Adair, Catherine H. Tinsley, Masako Taylor -- Culture and control : how independent and interdependent selves experience agency and constraint / Tanya Menon, Jeanne Ho-Ying Fu -- Managing challenges in multicultural teams / Kristin Behfar, Mary Kern, Jeanne Brett -- An emotion process model for multicultural teams / Hillary Anger Elfenbein, Aiwa Shirako -- Cultural intelligence and the multinational team experience : does the experience of working in a multinational team improve cultural intelligence? / Lisa M. Moynihan, Randall S. Peterson, P. Christopher Earley -- Toward an understanding of psychological distance reduction between generations : a cross-cultural perspective / Morela Hernandez, Ya-Ru Chen, Kimberly A. Wade-Benzoni -- Global work culture and global identity, as a platform for a shared understanding in multicultural teams / Efrat Shokef, Miriam Erez -- Bringing culture to the table ... / Marilynn B. Brewer -- Power, culture, and action : considerations in the expression and enactment of power in East Asian and Western societies / Chen-Bo Zhong, Joe C. Magee, William W. Maddux, Adam D. Galinsky -- A model of paternalistic organizational control and group creativity / Jing Zhou -- Dynamics of trust in guanxi networks / Roy Yong-Joo Chua, Michael W. Morris -- National culture and groups : an introduction / Ya-Ru Chen.
Print version record
Keywords: Business & Economics -- Management; Social Science -- Anthropology -- General; Organizational theory & behaviour; Group identity; Cultural pluralism